2009
DOI: 10.1080/02652040802372899
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the formulation components on the properties of the system SLN-dextran hydrogel for the modified release of drugs

Abstract: A system composed by solid lipid nanoparticles (SLN) entrapped into a chemical hydrogel of dextran was recently proposed for the controlled release of lipophilic drugs in oral formulations. This study reports now an extension of such study focused on the investigation of how the nature and the amount of the formulation components are able to modify the properties of the system. In particular the concentration of the two surfactants used for the nanosuspension stabilization, the nature of the lipid phase used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…It is well known and also shown by DSC measurements that the melting point of colloidal structures is lower than that of the bulk due to the influence of surface energy [44]. A difference in release profiles caused by a difference in lipid melting points was also suggested by Paolicelli et al [49]. The release of QSI was more prolonged in SLF showing < 20 % burst in all SLNs, Fig.…”
Section: In Vitro Release Of Qsisupporting
confidence: 60%
“…It is well known and also shown by DSC measurements that the melting point of colloidal structures is lower than that of the bulk due to the influence of surface energy [44]. A difference in release profiles caused by a difference in lipid melting points was also suggested by Paolicelli et al [49]. The release of QSI was more prolonged in SLF showing < 20 % burst in all SLNs, Fig.…”
Section: In Vitro Release Of Qsisupporting
confidence: 60%
“…It is well known that the melting point of colloidal structures may be lower than that of the bulk due to the influence of surface energy (Mader, 2006). A difference in release profiles caused by a difference in lipid melting points was also suggested by Paolicelli et al (2008) in a study with ibuprofen and acylglycerols differing in melting points. The higher amount released from trimyristate particles may also reflect the smaller size of these particles.…”
Section: Release Profiles Of Betamethasone-17-valerate Loaded Sln Depmentioning
confidence: 91%
“…Moreover, the decreased drug mobility at the experimental release temperature is a result of a higher melting point of Compritol. Paolicelli et al (34) reported a variation in the release profiles of ibuprofen and acylglycerols with different melting points and suggested that the reason for this variation was the difference in lipid melting points.…”
Section: In Vitro Release Study Of Slnsmentioning
confidence: 99%